Supply and Demand Analysis in Drinking Water and Sanitation Provision Programs - Perwira, Moch. Indra; Suhendi, Cece; Nugroho, Nadhya Susilo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Water is a vital resource for human life, both for domestic and non-domestic needs. However, the availability of clean water often faces challenges, especially in rural areas during the dry season. This study aims to analyze the balance of water supply and demand in the PAMSIMAS program in Kampung Gobang, which involves four neighborhood units (RT) with a total of 80 households. The research used a descriptive quantitative method with a storage measurement approach to calculate water demand and supply during rainy and dry seasons. The results showed that during the rainy season, the water supply of 150,334 liters/day exceeded the community’s demand of 106,143.5 liters/day, while in the dry season the supply decreased to 95,040 liters/day, lower than the required demand. To address this shortage, water distribution was managed alternately among the RTs according to the proportion of households and daily water needs, resulting in RT 09 receiving 39,600 liters, RT 06 receiving 19,800 liters, RT 05 receiving 11,880 liters, and RT 04 receiving 23,760 liters within 24 hours. The findings suggest that although the supply is sufficient in the rainy season, demand cannot be fully met in the dry season, requiring a fair distribution strategy to minimize conflict and ensure equitable access to clean water.